A multiomics and network pharmacological study reveals the neuroprotective efficacy of Fu-Fang-Dan-Zhi tablets against glutamate-induced oxidative cell death. (September 2022) - Gu, Yu; Huang, Pengli; Cheng, Taofang; Yang, Jian; Wu, Gaosong; Sun, Yuting; Liu, Aijun; Li, Houkai; Zhao, Jing; Ye, Ji
Abstract: Neuroprotective therapy after ischemic stroke remains a significant need, but current measures are still insufficient. The Fu-Fang-Dan-Zhi tablet (FFDZT) is a proprietary Chinese medicine clinically employed to treat ischemic stroke in the recovery period. This work aims to systematically investigate the neuroprotective mechanism of FFDZT. A systems strategy that integrated metabolomics, transcriptomics, network pharmacology, and in vivo and in vitro experiments was used. First, middle cerebral artery occlusion (MCAO) model rats were treated with FFDZT. FFDZT treatment significantly reduced the infarct volume in the brains of middle cerebral artery occlusion (MCAO) model rats. Then, samples of serum and brain tissue were taken for metabolomics and transcriptomics studies, respectively; gene expression profiles of MCF7 cells treated with FFDZT and its 4 active compounds (senkyunolide I, formononetin, drilodefensin, and tanshinone IIA) were produced for CMAP analysis. Computational analysis of metabolomics and transcriptomics results suggested that FFDZT regulated glutamate and oxidative stress-related metabolites (2-hydroxybutanoic acid and 2-hydroxyglutaric acid), glutamate receptors (NMDAR, KA, and AMPA), glutamate involved pathways (glutamatergic synapse pathway; d -glutamine and d -glutamate metabolism; alanine, aspartate and glutamate metabolism), as well as the reactive oxygen species metabolic process. CMAP analysis indicated that two active ingredients of FFDZT (tanshinone ⅡA and senkyunolide I) could act as glutamate receptor antagonists. Next, putative therapeutic targets of FFDZT's active ingredients identified in the brain were collected from multiple resources and filtered by statistical criteria and tissue expression information. Network pharmacological analysis revealed extensive interactions between FFDZT's putative targets, anti-IS drug targets, and glutamate-related enzymes, while the resulting PPI network exhibited modular topology. The targets in two of the modules were significantly enriched in the glutamatergic synapse pathway. The interactions between FFDZT's ingredients and important targets were verified by molecular docking. Finally, in vitro experiments validated the effects of FFDZT and its ingredients in suppressing glutamate-induced PC12 cell injury and reducing the generation of reactive oxygen species. All of our findings indicated that FFDZT's efficacy for treating ischemic stroke could be due to its neuroprotection against glutamate-induced oxidative cell death. Graphical abstract: Image 1 Highlights: In vivo experiment illustrated FFDZT's efficacy to reduce infarct volumes. Diffusion kernel algorithm was used to construct metabolic modules. Multi-omics results suggested FFDZT's regulation to cellular oxidative stress. CMAP analysis implied FFDZT's two ingredients were glutamate receptor antagonists. 76 non-random targets expressed in brain were analyzed by network pharmacology.